Atypical magnetic resonance imaging findings in hypoxic brain injury - Maryam, Tooba; Gupta, Amul (Indian Journal of Case Reports, 2025)
Here, we present the case of hypoxic brain injury in a 50-year-old male patient who was found unconscious by his colleagues in the bathroom when he didn’t return for some time. On magnetic resonance imaging (MRI), there were symmetrical T2/fluid-attenuated inversion recovery hyperintensities seen involving the cortical gray matter of bilateral temporal, parietal, and occipital lobes with thickening of the cortex and effacement of overlying sulci. These areas showed acute restriction of diffusion. The findings on MRI were suggestive of hypoxic brain injury. Hypoxic brain injury in adults can be due to drowning, asphyxiation, carbon monoxide poisoning, or cardiac arrest. The gas geyser syndrome causing hypoxic brain injury due to carbon monoxide poisoning is not a very uncommon occurrence in India as the use of gas geysers with poor ventilation in bathrooms is quite common.